Accuracy of prognosis estimates by four palliative care teams: a prospective cohort study - Higginson, Irene J (BioMed Central, 2002)
BACKGROUND: Prognosis estimates are used to access services, but are often inaccurate. This study aimed to determine the accuracy of giving a prognosis range. METHODS AND MEASUREMENTS: A prospective cohort study in four multi-professional palliative care teams in England collected data on 275 consecutive cancer referrals who died. Prognosis estimates (minimum – maximum) at referral, patient characteristics, were recorded by staff, and later compared with actual survival. RESULTS: Minimum survival estimates ranged <1 to 364 days, maximum 7 – 686 days. Mean patient survival was 71 days (range 1 – 734). In 42% the estimate was accurate, in 36% it was over optimistic and in 22% over pessimistic. When the minimum estimate was less than 14 days accuracy increased to 70%. Accuracy was related, in multivariate analysis, to palliative care team and (of borderline significance) patient age. CONCLUSIONS: Offering a prognosis range has higher levels of accuracy (about double) than traditional estimates, but is still very often inaccurate, except very close to death. Where possible clinicians should discuss scenarios with patients, rather than giving a prognosis range.